Napaeus lajaensis sp. nov. (Gastropoda: Pulmonata: Enidae) from a Quaternary Aeolian Deposit of Northeast Tenerife, Canary Islands - Castillo, Carolina; Yanes, Yurena; Alonso, María R.; Ibáñez, Miguel (Zootaxa, 2006)
Napaeus lajaensis sp. nov. is the oldest Napaeus species found in the Canary Islands, with more than 130 ka. It is described from a Pleistocene aeolian deposit intercalated between two basaltic lava flows located at Mancha de La Laja (Tenerife Island). The new species is characterized mainly by the presence of two very prominent, spiral, semicylindrical ribs on the body whorl shell. The stratigraphic setting and taphonomic features of the land snail association to which N. lajaensis belongs, were also shown.